PENGARUH PENDEKATAN SAINTIFIK BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS TEKS PUISI SISWA KELAS VIII SMP NEGERI 12 PADANG - Syafutra, Salman; Agustina, Agustina; Asri, Yasnur (Universitas Negeri Padang, 2018)
ABSTRACT The purpose of this study is (1) to determine the level of skill of writing poetry text of grade VIII of SMP Negeri 12 Padang before using saintific approachwith audiovisual media. (2) to determine the level of writing’s skill on poetry text of grade VIII of SMP Negeri 12 Padang after using saintific approachwith audiovisual media. (3) analyze the effect application saintific approach with audiovisual media assisted to the skill of writing poetry text in grade VIII students of SMP Negeri 12 Padang. This type of research is quantitative experimental method. Based on data analysis, using saintific approachwith audiovisual media toward students writing’s skill on poetry text in grade VIII students of SMP Negeri 12 Padang. Kata kunci : pengaruh, pendekatan saintifik, media audiovisual, menulis teks puisi